Studi Literatur Pendidikan Anti Korupsi Pada Organisasi Sektor Publik - Edi Abral (Pusat Riset dan Inovasi Nasional, 2023)
Organizations are made up of people who react differently to the impact of corruption. Organizational integrity includes the integration of systems, operational organization, strategy, control, corruption, and ethical standards, thereby creating norms of behavior. Another misconception is that corruption originates from organizations, not the individuals within them, as if ethical violations in practice occur almost by osmosis from organizations that are not accountable to those individuals. Individual efforts to eradicate corruption are likely to be less successful than efforts made by organizations. The transfer of money from individuals into organizational dynamics can be seen in the case of criminal corporations. Disruption if the organization provides a structural framework that eliminates the possibility of practical corruption. The ability of individuals to interpret rules or decide whether to implement certain protocols should be avoided in systems that cannot be manipulated.